2019 IEEE 21st Conference on Business Informatics (CBI) 2019
DOI: 10.1109/cbi.2019.00037
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Value Creation through Big Data Analytics Capabilities: A Configurational Approach

Abstract: Despite the documented potential of Big Data Analytics Capabilities (BDAC), it is by no means clear how they support the capacity of firms to purposefully create, extend, or modify their resource bases, i.e., dynamic capabilities (DC). This study extends current literature by exploring and elucidating various contingent big data capabilities, resources, and conditions that lead to the formation of these DCs in today's turbulent business environment. We use a qualitative approach using a cross-interview study m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…BDAC is presently regarded as a game-changer to enable an organization's sustainable performance due to its great operational and strategic potential. The emerging literature establishes a positive correlation between BDAC and organizational performance in various industries [24,25,80,83,84]. Consistent with previous research, we regard BDAC as a critical dynamic capability contributing to sustainable performance in the current study environment.…”
Section: Bda Capabilitiessupporting
confidence: 88%
See 1 more Smart Citation
“…BDAC is presently regarded as a game-changer to enable an organization's sustainable performance due to its great operational and strategic potential. The emerging literature establishes a positive correlation between BDAC and organizational performance in various industries [24,25,80,83,84]. Consistent with previous research, we regard BDAC as a critical dynamic capability contributing to sustainable performance in the current study environment.…”
Section: Bda Capabilitiessupporting
confidence: 88%
“…The study of [80] stated that while the existing literature has numerous discussions on SCM's predictive analytics and data science, it fails to demonstrate a direct link between SSCM practices and BDAC. Similarly, a few studies have indicated that BDAC has a beneficial effect on SSCM; however, these studies are rare in number and do not use the same set of measures [80]. As a result, generalizations about the relationship between BDAC and SSCM practices must be established.…”
Section: Bda Capabilitiesmentioning
confidence: 99%
“…Big data analytics capabilities refer to incorporating big data into the organizational decision-making process (Rialti et al, 2019). This approach includes not only big data technical infrastructure, but human skills and the knowledge required to embrace, adopt and deploy data-driven insights extraction (Van De Wetering et al, 2019). BDAC can be divided into different factors: (1) tangible, such as technology and financial resources; and (2) intangible, which relates to human skills and knowledge (Gupta and George, 2016).…”
Section: Mediating Role Of Big Data Analytics Capabilities (Bdac) In the Relationship Between Open Innovation And Organizational Performamentioning
confidence: 99%
“…Due to the rapid expansion of information technology, big data analytics (BDA) can help organizations to apply the "largescale group decision-making" (LSGDM) strategy, which lowers relational and task conflicts among different SC stakeholders (Liu et al, 2020;Wu et al, 2017) and becoming the backbone of the current progressive growth. BDA capabilities (BDAC) have acquired strategic significance and have become one of the most precious assets of multiple organizations (Van De Wetering et al, 2019;Shamim et al, 2020). In a similar vein, organizations in many countries have been undergoing a surge in digitizing and acceptance of BDA technologies over the past few years (Wang et al, 2018;Gong and Janssen, 2020;Mikalef et al, 2020;Cetindamar et al, 2021;Shahbaz et al, 2021).…”
Section: Introductionmentioning
confidence: 99%